Role of Human Na,K-ATPase alpha 4 in Sperm Function, Derived from Studies in Transgenic Mice - McDermott, Jeffrey (Mol Reprod Dev, 2015)
Most of our knowledge on the biological role of the testis-specific Na,K-ATPase alpha 4 isoform derives from studies performed in non-human species. Here, we studied the function of human Na,K-ATPase alpha 4 after its expression in transgenic mice. Using a bacterial artificial chromosome (BAC) construct, containing the human ATP1A4 gene locus, we obtained expression of the human α4 transgene specifically in mouse sperm, enriched in the sperm flagellum. The expressed, human alpha 4 was active, and compared to wild-type sperm, those from transgenic mice displayed higher Na,K-ATPase alpha 4 activity and greater binding of fluorescently labeled ouabain, which is typical of the alpha 4 isoform. The expression and activity of endogenous alpha 4 and the other Na,K-ATPase alpha isoform present in sperm, alpha 1, remained unchanged. Male mice expressing the human ATP1A4 transgene exhibited similar testis size and morphology, normal sperm number and shape, and no changes in overall fertility compared to wild-type mice. Sperm carrying the human transgene exhibited enhanced total motility and an increase in multiple parameters of sperm movement, including higher sperm hyperactive motility. In contrast, no statistically significant changes in sperm membrane potential, protein tyrosine phosphorylation, or spontaneous acrosome reaction were found between wild-type and transgenic mice. Altogether, these results provide new genetic evidence for an important role of human Na,K-ATPase alpha 4 in sperm motility and hyperactivation, and establishes a new animal model for future studies of this isoform.